Marketing Strategy of Salted Fish Traders during the Covid-19 Pandemic (Case Study of Malabro Village, Kecamatan Teluk Segara, Kota Bengkulu) - Sili Maryani; Oka Media; Engga Junia Lesri; Miti Yarmunida; Andi Harpepen (Penerbit Jurnal Indonesia, 2021)
The Corona virus outbreak has an impact on the economy causing an economic crisis in the world. This study aims to determine the impact of the Covid-19 pandemic on the economy of salted fish traders and find out how the marketing strategy is to keep selling salted fish traders during the COVID-19 pandemic. This research uses qualitative research. The marketing strategy carried out by salted fish traders during the current covid-19 pandemic is to promote using social media such as: Facebook, WhatsApp and cell phones. In addition, other strategies carried out by salted fish traders are improving product quality and serving consumers well/friendly, maintaining communication (silahturahmi) to consumers and always maintaining cleanliness.